Shedding reduction and immunity modulation in piglets with an inactivated Mycoplasma hyopneumoniae vaccine encapsulated in nanostructured SBA-15 silica - Petri, Fernando Antonio Moreira [UNESP]; Malcher, Clarisse Sena [UNESP]; Mechler-Dreibi, Marina Lopes [UNESP]; Panneitz, Ana Karolina [UNESP]; Braga, Eduarda Ribeiro [UNESP]; Aguiar, Gabriel Alexandre de [UNESP]; Toledo, Leonardo Teófilo; Martins, Tereza Silva; Cides-da-Silva, Luis Carlos; Fantini, Márcia C.A.; Sant'Anna, Osvaldo A.; Montassier, Hélio J. [UNESP]; et al. (Elsevier, 2024)
Mycoplasma (M.) hyopneumoniae is a primary etiological agent of porcine enzootic pneumonia (PEP), a disease that causes significant economic losses to pig farming worldwide. Current commercial M. hyopneumoniae vaccines induce partial protection, decline in preventing transmission of this pathogen or inducing complete immunity, evidencing the need for improving vaccines against PEP. In our study, we aimed to test the effectiveness of the SBA-15 ordered mesoporous silica nanostructured particles as an immune adjuvant of a vaccine composed of M. hyopneumoniae strain 232 proteins encapsulated in SBA-15 and administered by intramuscular route in piglets to evaluate the immune responses and immune-protection against challenge. Forty-eight 24-day-old M. hyopneumoniae-free piglets were divided into four experimental groups with different protocols, encompassing a commercial vaccine against M. hyopneumoniae, SBA-15 vaccine, SBA-15 adjuvant without antigens and a non-immunized group. All piglets were challenged with the virulent strain 232 of M. hyopneumoniae. Piglets that received the SBA-15 and commercial vaccine presented marked immune responses characterized by anti-M. hyopneumoniae IgA and IgG antibodies in serum, anti-M. hyopneumoniae IgA antibodies in nasal mucosa and showed an upregulation of IL-17 and IL-4 cytokines and downregulation of IFN-γ in lungs 35 days post-infection. Piglets immunized with SBA-15 vaccine presented a reduction of bacterial shedding compared to piglets immunized with a commercial bacterin. In addition, piglets from SBA-15 adjuvant suspension group presented increased IL-17 gene expression in the lungs without involvement of Th1 and Th2 responses after challenge. These results indicated that SBA-15 vaccine induced both humoral and cell-mediated responses in the upper respiratory tract and lungs, first site of replication and provided protection against M. hyopneumoniae infection with a homologous strain with reduction of lung lesions and bacterial shedding. Finally, these results enhance the potential use of new technologies such as nanostructured particles applied in vaccines for the pig farming industry.
Keywords: Adjuvant; Nanotechnology; Porcine enzootic pneumonia; Th1; Th17; Upper respiratory tract